2018
DOI: 10.1186/s13049-018-0575-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of gasping for short and long outcomes during out-of-hospital cardiac arrest: an updated systematic review and meta-analysis

Abstract: ObjectiveWe systematically reviewed the literature to investigate whether gasping could predict short and long outcomes in patients with out of hospital cardiac arrest (OHCA).MethodsPubMed, Embase, and Cochrane Library were searched for observational studies regarding the prognostic effect of gasping on short and long outcomes in adults with OHCA. The primary outcome was return of spontaneous circulation (ROSC). The secondary outcomes were favorable neurological outcome at discharge or at 30 days after cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“… 6 A systematic review investigated whether agonal breathing predicts short-term and long-term outcomes in OHCA. 7 The review, which included five studies, showed that agonal breathing was associated with a significant increase in the rate of return of spontaneous circulation (risk ratio [RR], 1.87; 95% CI, 1.64–2.13) and with a higher likelihood of favorable neurological outcomes (RR, 3.79; 95% CI, 1.86–7.73) and increased long-term survival (≥6 months) (RR, 3.46; 95% CI, 1.70–7.07) 6 , 16 , 17 , 18 . Debaty G. 2017 et al, reported that the combination of agonal breathing and appropriate initial shock waveform for electrical shock application had higher for favorable patient outcomes compared to no agonal breathing and no shockable rhythm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 A systematic review investigated whether agonal breathing predicts short-term and long-term outcomes in OHCA. 7 The review, which included five studies, showed that agonal breathing was associated with a significant increase in the rate of return of spontaneous circulation (risk ratio [RR], 1.87; 95% CI, 1.64–2.13) and with a higher likelihood of favorable neurological outcomes (RR, 3.79; 95% CI, 1.86–7.73) and increased long-term survival (≥6 months) (RR, 3.46; 95% CI, 1.70–7.07) 6 , 16 , 17 , 18 . Debaty G. 2017 et al, reported that the combination of agonal breathing and appropriate initial shock waveform for electrical shock application had higher for favorable patient outcomes compared to no agonal breathing and no shockable rhythm.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Previous studies in OHCA have reported that patients with agonal breathing have a 3.5 times higher survival rate than those without agonal breathing. 6 , 7 Additionally, in a study in which extracorporeal CPR (ECPR) was performed on patients who had agonal breathing during EMS transport, it served as a prognostic factor for improved outcomes. 8 However, this study did not examine patients with agonal breathing while on no ECPR during EMS Transport.…”
Section: Introductionmentioning
confidence: 99%
“…Agonal breathing can be a predictor of whether a patient is experiencing a cardiac arrest or not. If agonal breathing is detected, then there is a high probability that the initial rhythm of the patient is one that is conducive to defibrillation 71 . Researchers have found that in approximately 20-25% of the OHCA calls; cardiac arrest is not confirmed due to the uncertainty of the patient's breathing 65,58,59,72,4,69 .…”
Section: Confirmation Of Cardiac Arrestmentioning
confidence: 99%
“…As part of the assessment to determine whether an OHCA has occurred, the dispatchers must confirm the patient's responsiveness and their breathing pattern 63 . From these two medical signs, the caller can accurately determine the patient's responsiveness but may not accurately identify and describe the patient's breathing pattern to the dispatcher, causing delayed or incorrect assessment 58,71,72 . Many studies have been published that have analyzed the audio recordings from dispatch centers to determine the cause for delayed or missed diagnosis of cardiac arrest events 68,36,69 .…”
Section: Confirmation Of Cardiac Arrestmentioning
confidence: 99%
“…24,25 Agonal respiration is an early sign of CA and studies indicate it is significantly associated with a high likelihood of initial shockable rhythm, which may contribute to good neurological outcomes. [25][26][27] Lay rescuers, however, usually do not consider this movement as a sign of CA and report that CA victims with agonal respiration are unconscious, but still breathing.…”
Section: Agonal Respirationmentioning
confidence: 99%